2021
DOI: 10.1002/vrc2.5
|View full text |Cite
|
Sign up to set email alerts
|

Right‐sided congestive heart failure secondary to supraventricular tachycardia in a dog with a right atrial mass

Abstract: A dog was referred to the authors' hospital for further investigations of pelvic limb collapsing episodes. Physical examination revealed a positive hepatojugular reflux, positive fluid thrill on abdominal palpation and an irregular heart rhythm (144 bpm) with pulse deficits. A six-lead ECG showed focal atrial tachycardia. Doppler echocardiography revealed systolic dysfunction, dilated cardiomyopathy phenotype and the presence of a heterogeneous mass in the right atrium; this was confirmed by a CT study. Free a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Primary cardiac tumours have been previously associated with arrhythmias, but most commonly bradyarrhythmias such as atrioventricular block 16,17 . As presented in this case, supraventricular tachycardia has been previously reported in association with a right atrial mass, but a causal relationship between tumour and arrhythmia could not be confirmed 18 . Furthermore, a primary endocardial pleomorphic sarcoma was reported to cause a left ventricular outflow obstruction, with a complex arrythmia, involving sinus arrest, junctional escape rhythm and periods of ventricular tachcardia 19 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Primary cardiac tumours have been previously associated with arrhythmias, but most commonly bradyarrhythmias such as atrioventricular block 16,17 . As presented in this case, supraventricular tachycardia has been previously reported in association with a right atrial mass, but a causal relationship between tumour and arrhythmia could not be confirmed 18 . Furthermore, a primary endocardial pleomorphic sarcoma was reported to cause a left ventricular outflow obstruction, with a complex arrythmia, involving sinus arrest, junctional escape rhythm and periods of ventricular tachcardia 19 .…”
Section: Discussionmentioning
confidence: 63%
“…16,17 As presented in this case, supraventricular tachycardia has been previously reported in association with a right atrial mass, but a causal relationship between tumour and arrhythmia could not be confirmed. 18 Furthermore, a primary endocardial pleomorphic sarcoma was reported to cause a left ventricular outflow obstruction, with a complex arrythmia, involving sinus arrest, junctional escape rhythm and periods of ventricular tachcardia. 19 The tricuspid valve origin of myxoma has been reported previously in the dog, 15 but association with the tricuspid valve would be less likely with right atrium HSA.…”
Section: Discussionmentioning
confidence: 99%